2018
DOI: 10.1002/cjce.23153
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of CO2 adsorption on biochar derived from biomass pyrolysis in molten salt

Abstract: This work focused on the preparation and characterization of a promising biochar as a novel solid adsorbent towards CO2. The biochar was prepared by catalytic pyrolysis of waste roasted peanut shell in molten salt; it was characterized by means of SEM‐EDS, BET, FTIR, and TGA, followed by determining the adsorption characteristics, such as adsorption capacity, isosteric heat of adsorption, uptake rate, and selectivity via adsorption temperature and gas pressure. The results indicated that the as‐prepared biocha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…As seen from Figure , the raw biochar exhibited different FTIR spectra than the pristine coconut shell. The intense bands near 3422 cm −1 (N‐H stretching vibration of amino derivatives and O‐H stretching vibration were probably due to the presence of and interaction between the alcoholic, phenolic, amino, and carboxylic derivatives from macromolecules, such as cellulose, hemicellulose, and lignin) became obviously weak, which indicated that some compounds containing the groups of N‐H and O‐H were released during the raw biochar preparation, such as NH 3 and H 2 O. Meanwhile, the intense bands between 2800 cm −1 ‐3000 cm −1 (assigned to the C‐H stretching vibration of methyl and methylene groups) became weak, which meant that some groups of methyl and methylene disappeared in addition to the release of carbon‐containing compounds such as C 2 H 6 during the carbonization stage of the pristine coconut shell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As seen from Figure , the raw biochar exhibited different FTIR spectra than the pristine coconut shell. The intense bands near 3422 cm −1 (N‐H stretching vibration of amino derivatives and O‐H stretching vibration were probably due to the presence of and interaction between the alcoholic, phenolic, amino, and carboxylic derivatives from macromolecules, such as cellulose, hemicellulose, and lignin) became obviously weak, which indicated that some compounds containing the groups of N‐H and O‐H were released during the raw biochar preparation, such as NH 3 and H 2 O. Meanwhile, the intense bands between 2800 cm −1 ‐3000 cm −1 (assigned to the C‐H stretching vibration of methyl and methylene groups) became weak, which meant that some groups of methyl and methylene disappeared in addition to the release of carbon‐containing compounds such as C 2 H 6 during the carbonization stage of the pristine coconut shell.…”
Section: Resultsmentioning
confidence: 99%
“…KOH was often used as an activator for obtaining such biochar with a high specific surface area and advanced porosity. Shell biochar derived from KOH activation was often used for CO 2 uptake . However, there are few reports on the formation mechanism of the porous structure and characteristics of CO 2 adsorption on coconut shell‐derived biochars derived from biomass catalytic pyrolysis within moderate‐temperature IL, such as adsorption capacity, adsorption potential, isosteric heat, and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The specific surface area and pore size distribution were obtained according to the N 2 adsorption‐desorption isotherms of the complex . The surface functional groups of the complex were evaluated based on Fourier transform infrared spectroscopy (FTIR) . Then, the pyrolysis behaviour of the complex was investigated using a thermal gravimetric analyzer (Q600 SDT, TA Instrument, USA) under flowing nitrogen and air (20 mL/min).…”
Section: Methodsmentioning
confidence: 99%
“…The adsorption isotherms of CO 2 were experimentally obtained using a volumetric gas adsorption method . The capacities of CO 2 captured by the adsorbents (70–100 mg for testing) were analyzed during every pressure step in the pressure range from 0–100 kPa.…”
Section: Methodsmentioning
confidence: 99%
“…LCO has the properties of high density, high aromatic content, and low hydrogen content in China, and it accounts for 30 % of the diesel. Catalytic hydrogenation technology can convert low‐value LCO into a high‐octane gasoline blending component, achieving the high‐value utilization of LCO . Therefore, in the area of LCO hydrotreating, the study of hydrogenation performance of the modified zeolite still needs to be investigated further.…”
Section: Introductionmentioning
confidence: 99%